Short Communication: Molecular barcode and morphology analysis of Malva pseudolavatera Webb & Berthel and Malva sylvestris L. from Ecuador - GLENDA SARMIENTO-TOMALÁ; Efrén Santos-Ordóñez; MIGDALIA MIRANDA-MARTÍNEZ; RICARDO PACHECO-COELLO; RAMÓN SCULL-LIZAMA; YAMILET GUTIÉRREZ-GAITÉN; RENÉ RENÉ DELGADO-HERNÁNDEZ (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Sarmiento-Tomalá G, Santos-Ordóñez E, Miranda-Martínez M, Pacheco-Coello R, Scull-Lizama R, Gutiérrez-Gaitén Y, Delgado-Hernández R. 2020. Short Communication: Molecular barcode and morphology analysis of Malva pseudolavatera Webb & Berthel and Malva sylvestris L from Ecuador. Biodiversitas 21: 3554-3560. In Ecuador, several plant species are used in traditional medicine without a criterion of family, genera, or chemical composition. The species of the genus Malva (Malva pseudolavatera Webb & Berthel and Malva sylvestris L), introduced in Ecuador, are widely used by the population; however, unlike the species M. sylvestris, for M. pseudolavatera there is no information about its composition and properties. Plant material was collected in the province of Chimborazo in Ecuador and taxonomic classification was performed. Histological study was performed in leaves and powder drug. Molecular barcodes were generated using the ribulose bisphosphate carboxylase large chain (rbcL), maturase K (matK), internal transcribed spacer 1 (ITS1) and ITS2 sequences. Micro-morphological analysis revealed that no major structural differences were observed between the two species. Sequence analysis of molecular barcodes revealed that samples of the different species showed a close relation to each other due to the high percentage of similarity. The ITS sequences showed that the two samples correspond to different species of Malva; while for the rbcL and matK, interspecies differentiation could not be detected. Therefore, ITS could be used for interspecific analysis.